Analysis of Economic Growth and Tourism Potential in Tanjung Lesung, Panimbang, Banten as a Creative Economy Destination - Rizki Apriva Hidayana; Mugi Lestari (International Journal of Business, Economics, and Social Development, 2025)
Tanjung Lesung, located in Pandeglang Regency, Banten, has been designated as a Special Economic Zone (SEZ) for Tourism with the aim of encouraging regional economic growth and improving community welfare. This study analyzes the impact of SEZ on the local economy using qualitative and quantitative approaches. Data were obtained through in-depth interviews, surveys, field observations, and documentation studies. The results of the study indicate that the Tanjung Lesung SEZ has contributed positively to increasing community income by 52% and reducing the unemployment rate by 33%. In addition, investment in the tourism sector encourages business growth in the hospitality, culinary, and tourism services sectors. However, the development of SEZ also faces several challenges, such as limited infrastructure, readiness of local workers, and social and environmental impacts. Limited infrastructure, especially transportation access, is an obstacle in supporting the growth of the tourism sector. In addition, many local workers do not yet have the skills needed by the tourism industry. Environmental impacts, such as increasing waste volume and conversion of agricultural land, are also major concerns. Therefore, a comprehensive strategy is needed through improving infrastructure, strengthening human resource capacity, and implementing sustainable environmental management policies. With the right steps, Tanjung Lesung Special Economic Zone can become a successful model for inclusive and sustainable tourism-based economic development in Indonesia.